THE EFFECT OF CUSTOMER REVIEW AND CELEBRITY ENDORSEMENT TOWARD INDONESIA LOCAL MAKEUP BRAND PURCHASE INTENTION - Christianie, Gabriella; Sihombing, Tanggor (2021)
This study aims to determine the effect of customer reviews and celebrity endorsements on the purchase intention of local makeup brand products in Indonesia. This study has sample from 257 people, who are potential customers or consumers of local makeup brands in Indonesia. The variables in this study are purchase intention as the dependent variable, while the independent variables in this study are customer reviews, celebrity endorsements, and trust as moderating variable. This study uses quantitative research methods, where the data collected is processed using the structural equation modelling (SEM) method using SmartPLS. This study found that celebrity endorsements affect purchase intention, but customer review and trust do not affect or moderate customer reviews and celebrity endorsements.